2009
DOI: 10.1097/pec.0b013e31819a7e20
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Observation Unit and an Emergency Department-Admitted Patient Transfer Mandate in Decreasing Overcrowding in a Pediatric Emergency Department

Abstract: Simulation scenario analyses predict that an OU and a transfer mandate would reduce overcapacity in the PED, with more substantial reductions in time to be seen and length of stay for patients of high acuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Variations in reimbursement may limit hospital efforts to refine models of observation care for children. Designated OUs have been suggested as a method for improving ED patient flow, 26 increasing inpatient capacity, 27 and reducing costs of care. 28 Standardization of observation status criteria and consistent reimbursement for observation services may be necessary for hospitals to develop operationally and physically distinct OUs, which may be essential to achieving the proposed benefits of observation medicine on costs of care, patient flow, and hospital capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in reimbursement may limit hospital efforts to refine models of observation care for children. Designated OUs have been suggested as a method for improving ED patient flow, 26 increasing inpatient capacity, 27 and reducing costs of care. 28 Standardization of observation status criteria and consistent reimbursement for observation services may be necessary for hospitals to develop operationally and physically distinct OUs, which may be essential to achieving the proposed benefits of observation medicine on costs of care, patient flow, and hospital capacity.…”
Section: Discussionmentioning
confidence: 99%
“…This proposition was supported in the real world by Han et al ,106 who reported no change in ambulance diversion and an increase in ED LOS, when the number of beds in their ED was doubled. Viccelio et al 107 have demonstrated the safety of a protocol allowing patients to be ‘pushed’ into inpatient hallways, but did not study the effect on crowding, while Hung and Kissoon108 (computer modelling) and Quinn et al 109 (real world) demonstrated a small reduction in ED LOS +/− ambulance diversion when patients were transferred directly into inpatient beds without waiting to be reviewed by inpatient teams. The best-studied intervention is the use of holding units, observation units or assessment units to decant patients from the ED.…”
Section: Solutions For Crowdingmentioning
confidence: 99%
“…Patients in EDs may experience long delays when ED rooms are being used by patients needing ongoing treatment or awaiting an inpatient bed. A computer simulation study at the Children' s Hospital in Vancouver British Columbia 43 revealed that an OU would reduce wait times in the pediatric ED by creating additional capacity and improving patient flow.…”
Section: Effect Of Ous On Inpatient Hospital Utilizationmentioning
confidence: 99%